Correction: Fabrication of a graphene coated nonwoven textile for industrial applications. Issue 86 (31st August 2016) - Kongahage, Dharshika; Foroughi, Javad; Gambhir, Sanjeev; Spinks, Geoffrey M.; Wallace, Gordon G.
Abstract : Correction for 'Fabrication of a graphene coated nonwoven textile for industrial applications' by Dharshika Kongahge et al., RSC Adv., 2016, 6, 73203–73209.